Trade Openness and Cross-country Income Differences - Christian Hepenstrick; Alexander Tarasov (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
Development accounting literature usually attributes the observed cross-country variation in per capita income to differences in countries' factor endowments and total factor productivity (the Solow residual). While the former can be relatively straightforward interpreted and measured, the latter remains at least partly a black box. In this paper, we provide a structural interpretation for differences in total factor productivity across countries and quantitatively explore the role of trade barriers in explaining cross-country income differences. In particular, we find that giving all countries the same market entry costs or giving all country-pairs the same variable trade costs reduces inequality by around 13%.
urn:nbn:de:bvb:19-epub-15421-8
Keywords: F11; F12; O10; O40; 330; General equilibrium; market access costs; development accounting; experiments